Strategi Metode Dialogis Pembelajaran Pendidikan Kewarganegaraan Terhadap Prestasi Belajar Siswa SMP Negeri 1 Kaliorang Kabupaten Kutai Timur - Helentina Hutajulu (Peneliti.net, 2021)
This Classroom Action Research (CAR) aims to improve the learning achievement of Citizenship Education students in the material for Developing Life and Hope with the Dialogical learning model at SMP Negeri 1 Kaliorang. The problem currently being faced is the low learning achievement of students in learning Citizenship Education. The purpose of this study was to develop a strategy of learning the dialogue method of Citizenship Education. The research is quasi-experimental which provides certain treatment, namely the dialogical method. This research was conducted on 63 students of class VIII at SMPN 1. The method of collecting data is by observing, observing and assessing learning achievement. Data collection methods used were observation, and written tests. Data analysis using Wilcoxon test. The results showed that there were differences in learning achievement before and after being given the dialogical method with indicators of student enthusiasm (p = 0.001), fluency of ideas (p = 0.001), activeness (p = 0.001), ability (p = 0.001), accuracy (p = 0.001 ) activeness in asking (p=0.001), activeness of students in finding learning resources (p=0.001), fluency of students in answering questions (p=0.001). The results show that the dialogical method is effective in improving student achievement. Teachers need to approach students to provide motivation so that self-confidence is formed.